Stereoselective degradation and thyroid endocrine disruption of lambda-cyhalothrin in lizards (Eremias argus) following oral exposure. (January 2018) - Chang, Jing; Hao, Weiyu; Xu, Yuanyuan; Xu, Peng; Li, Wei; Li, Jianzhong; Wang, Huili
Abstract: The disturbance of the thyroid system and elimination of chiral pyrethroid pesticides with respect to enantioselectivity in reptiles have so far received limited attention by research. In this study, bioaccumulation, thyroid gland lesions, thyroid hormone levels, and hypothalamus-pituitary-thyroid axis-related gene expression in male Eremias argus were investigated after three weeks oral administration of lambda-cyhalothrin (LCT) enantiomers. In the lizard liver, the concentration of LCT was negatively correlated with the metabolite-3-phenoxybenzoic acid (PBA) level during 21 days of exposure. (+)-LCT exposure induced a higher thyroid follicular epithelium height than (−)-LCT exposure. The thyroxine levels were increased in both treated groups while only (+)-LCT exposure induced a significant change in the triiodothyronine (T3) level. In addition, the expressions of hypothalamus-pituitary-thyroid axis-related genes including thyroid hormone receptors ( trs ), deiodinases ( dios ), uridinediphosphate glucuronosyltransferase ( udp ), and sulfotransferase (sult ) were up-regulated after exposure to the two enantiomers. (+)-LCT treatment resulted in higher expression of trs and (−)-LCT exposure led to greater stimulation of dios in the liver, which indicated PBA-induced antagonism on thyroid hormone receptors and LCT-induced disruption of thyroxine (T4) deiodination. The results suggest the (−)-LCT exposure causes higher residual level in lizard liver while induces less disruption on lizard thyroid activity than (+)-LCT. Graphical abstract: Highlights: The concentration of LCT was negatively correlated with the PBA level in liver. (+)-LCT exposure induced higher follicular epithelium height than (−)-LCT exposure. (−)-LCT exposure caused interruption of thyroxine deiodination. (+)-LCT treatment more seriously affected the thyroid hormone receptor genes. Abstract : The two enantiomers of LCT act via different toxic mechanism in the lizard thyroid system.